Morphological Characteristics and Phylogenetic Relationship of Several Genotypes of Coconut (Cocos nucifera L.) in Silau Laut District Asahan Regency - Risma Damayanti; Luthfi Aziz Mahmud Siregar; Diana Sofia Hanafiah (Universitas Sumatera Utara, 2018)
This research aimed to identify the morphological characteristics and phylogenetic relationship of several genotypes of coconut in Silau Laut district Asahan regency Sumatera Utara. The research was conducted from April to Mei 2017 by survey method based on coconut descriptor of International Plant Genetic Resources Institute (IPGRI) with sampling technique using accidental sampling. This result of research showed that in Silau Laut district there were 27 genotypes of coconut been identified. The result of morphologycal characteristics for crown shape (spherical, hemispherical, X-shaped ‘silhouette’), flower shape (normal and additional spathes or bracts), fruit shape (oblong, ovoid, angled, round), nut shape (pointed, ovoid, almost round, oblate). The closest phylogenetic relationship is G41 and G42 with coefficient dissimilarity 3,00 and farthest phylogenetic relationship is G40 and G45 with coefficient dissimilarity 12,53. The result of dendogam showed at scale 18 was formed 5 goups. Phylogenetic relationship of between genotypes of coconut in Silau Laut district Asahan regency still have a close level relationship.